Antibiotic susceptibility, antibacterial activity and probiotic characterisation of isolated Lactobacillus brevis strains from Heterotrigona itama honey - Nor Hazwani Hasali,; Amir Izzwan Zamri,; Mohd Nizam Lani,; Aidilla Mubarak, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Heterotrigona itama (Family: Apidae, Tribe: Meliponini, Genus: Trigona) is one of the stingless bee in Meliponiculture in Malaysia. H. itama honey is reported to be a good reservoir for novel lactic acid bacteria (LAB) with probiotic properties. In this study, five Lactobacillus brevis strains (strain Ibr-42, strain 37901, strain ATCC 367, strain NJ42 and strain KLDS) were previously isolated and identified from H. itama honey obtained from local stingless beekeepers in the coastal areas in Kelantan and Terengganu, were evaluated for antibiotic resistance, antibacterial activity, resistance to low pH, tolerance to bile salts and haemolytic activity. The results indicated that all five strains of L. brevis were susceptible to chloramphenicol, ampicillin, erythromycin, and tetramycin, but resistant to kanamycin. In terms of antagonistic activity among L. brevis, it was found antagonistic activity was minimum. For antibacterial activities of these strains against selected foodborne pathogenic bacteria by well diffusion method, L. brevis strain NJ42 exhibited the highest inhibition (24 mm) against Pseudomonas aeruginosa ATCC 15442. All Lactobacillus strains from H. itama honey were able to survive in pH 2 and 0.3% (w/v) bile salts concentration that mimic the conditions in the gastrointestinal system. The inability of L. brevis strains to exhibit β- haemolytic activity showing that haemolysis is not the virulence factor for these strains. These findings proved the isolated L. brevis in H. itama honey could be used as potential probiotic, envisaging its potential as one of functional foods for food industry.